Recent progress in understanding the persistent luminescence in SrAl2O4:Eu,Dy - Vitola, Virginija; Millers, Donats; Bite, Ivita; Smits, Krisjanis; Spustaka, Agnese (Taylor and Francis Ltd., 2019)
Ever since the discovery of SrAl2O4:Eu,Dy persistent afterglow material, that can intensively glow up to 20 h, the mechanism of long-lasting luminescence has been a popular area of research. The research is focused on discovering the mechanism of persistent luminescence in order to prolong the duration and intensity of afterglow in a controlled way. Although most researchers agree on the general things, there are still many unclarities and ambiguities to discuss upon. This review paper briefly sketches in the highlights of past research on the luminescence mechanism in SrAl2O4:Eu,Dy, mainly focusing on the research conducted in the past decade dedicated to clearing these ambiguities. This paper provides an overview of the latest persistent luminescence mechanisms offered by researchers.
This work was conducted with the funding of Scientific Research Project for Students and Young Researchers realised at the Institute of Solid State Physics, University of Latvia [SJZ/2018/2].
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; long afterglow; luminescence mechanism; Persistent luminescence; strontium aluminate